RNase A Inhibits Formation of Neutrophil Extracellular Traps in Subarachnoid Hemorrhage - Früh, Anton; Tielking, Katharina; Schoknecht, Felix; Liu, Shuheng; Schneider, Ulf C.; Fischer, Silvia; Vajkoczy, Peter; Xu, Ran (Frontiers in Physiology, 2021)
Background: Subarachnoid hemorrhage (SAH) caused by rupture of an intracranial aneurysm, is a life-threatening emergency that is associated with substantial morbidity and mortality. Emerging evidence suggests involvement of the innate immune response in secondary brain injury, and a potential role of neutrophil extracellular traps (NETs) for SAH-associated neuroinflammation. In this study, we investigated the spatiotemporal pattern of NETs in SAH and the potential role of the RNase A (the bovine equivalent to human RNase 1) application on NET burden. Methods: Male C57Bl/6 mice were operated utilizing a filament perforation model to induce SAH, and Sham operation was performed for the corresponding control groups. To confirm the bleeding and exclude stroke and intracerebral hemorrhage, the animals received Magnetic Resonance Imaging (MRI) after 24 hours. Mice were treated with intravenous injection of RNase A (42 µg/kg body weight) or saline solution for the control groups, respectively. Quadruple-immunofluorescence (IF) staining for cell nuclei (DAPI), F-actin (phalloidin), citrullinated H3 and neurons (NeuN) was analyzed by confocal imaging and used to quantify NET abundance in the subarachnoid space (SAS) and brain parenchyma. To quantify NETs in human SAH patients, cerebrospinal spinal fluid (CSF) and blood samples from day 1, 2, 7, and 14 after bleeding onset were analyzed for double-stranded DNA (dsDNA) via Sytox Green. Results: NETs are released upon subarachnoid hemorrhage in the subarachnoid space (SAS) on the ipsilateral bleeding site 24 hours after ictus. Over time, NETs showed progressive increase in the parenchyma on both ipsi- and contralateral site, peaking on day 14 in periventricular localization. In CSF and blood samples of patients with aneurysmal SAH, NETs also increased gradually over time with a peak on day 7. RNase application significantly reduced NET accumulation in basal, cortical and periventricular areas. Conclusion: NET formation following SAH originates in the ipsilateral subarachnoid space (SAS) of the bleeding site and spreads gradually over time to basal, cortical and periventricular areas in the parenchyma within 14 days. Intravenous RNase application abrogates NET burden significantly in the brain parenchyma, underpinning a potential role in modulation of the innate immune activation after SAH.